Unveiling the Constructed Identity of Santris: A Stylistic Exploration - Wulandari , Dwi; Santosa, Riyadi; ., Djatmika; Abdullah, Wakit R. (Journal of Ecohumanism, 2024)
This article aims at finding how santris living at modern pesantren construct their identities. The study is conducted at MBI AU a pesantren in Mojokerto, East Java with 156 respondents, 79 males and 77 females. The data are taken from their chats in WhatsApp groups for private contexts and from book communication and their public performance for public context. Interview is also conducted to support the data. The study reveals that at the macro level, santris, both males and females are not different from teenagers in general. At the meso level, santris are differentiated into the speakers of the east Javanese dialect (EJ), Non-east Javanese dialect (NEJ), and Non-Javanese (NJ). In this level, male santris of EJ tend to show a stronger Javanese identity compared to the females who show more accommodating natures. The NEJ and NJ santris are showing a higher tendency of doing relation of adequation toward the East Javanese dialect suggesting the drives for social allegiances and instrumental attachment toward the East Javanese dialect. Unlike the NJ santris who tend to show their home language as their self-constructed identity, the NEJ santris are using more bahasa gaul to distinguish themselves from the EJ santris.